Enhanced energy detection using matched filter for spectrum sensing in cognitive radio networks - Sarker, Pramit Likhan; Salama, Umme (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.